Student-Peer Mentoring on a Drug Information Response - Rodis, Jennifer Lin (American Journal of Pharmaceutical Education, 2014)
Objective. To implement a student peer-mentoring program with a drug information response assignment in an introductory pharmacy practice course. Design. Second-year student pharmacists (P2 mentors) enrolled in an independent study course were randomly assigned first-year student pharmacists (P1 mentees) to mentor on a drug information assignment. The P2 mentors provided feedback to P1 mentees' assignment drafts. The P1 mentees had the opportunity to revise the draft prior to turning in the completed assignment to course faculty members for grading. Assessment. Both P1 mentees and P2 mentors agreed the mentorship improved their ability to prepare a drug information response (76% and 100%, respectively). A majority of the student pharmacists would choose to be involved in the program again. Conclusion. The student peer-mentoring program was successful in improving student pharmacists' perceptions of ability to compose a drug information response.